2001
DOI: 10.1016/s0379-7112(01)00037-6
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental principles of structural behaviour under thermal effects

Abstract: This paper presents theoretical descriptions of the key phenomena that govern the behaviour of composite framed structures in fire. These descriptions have been developed in parallel with large scale computational work undertaken as a part of a research project (The DETR-PIT Project, Behaviour of steel framed structures under fire conditions) to model the full-scale fire tests on a composite steel framed structure at Cardington (UK). Behaviour of composite structures in fire has long been understood to be domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(153 citation statements)
references
References 4 publications
3
145
0
5
Order By: Relevance
“…A clean stability failure mechanism is clearly indicated by a simple computational analysis. Not only this, the analysis is entirely consistent with the fundamental principles developed during the Cardington work [2]. The following sections report in reasonable detail the various steps of the analysis undertaken…”
Section: The Aim Of This Worksupporting
confidence: 68%
See 2 more Smart Citations
“…A clean stability failure mechanism is clearly indicated by a simple computational analysis. Not only this, the analysis is entirely consistent with the fundamental principles developed during the Cardington work [2]. The following sections report in reasonable detail the various steps of the analysis undertaken…”
Section: The Aim Of This Worksupporting
confidence: 68%
“…Computational modelling and analytical studies [1,2] at Edinburgh University have shown that of these two competing effects in large frame structures, the former dominates the behaviour of the structure in the early stages while the latter becomes important near failure. In this paper structural behaviour is interpreted by analysing the typical structural responses to loading, namely, strains and stresses and more importantly their resultants (integrals), i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metal profiles are composed of aluminium or steel elements connected with thermal separator (three-chamber profiles) [30]. In case of metal profiles, it is essential to proper fill in their section in order to ensure insulation of the profiles and reduce the adverse impacts of the thermal stress [31]. Inside the profiles there are placed special insulating inserts usually made of gypsum plasterboards, silicate -cement boards, silicate -calcium boards or mineral wool plates, although on the market are also present solutions with timber infill [32], [33].…”
Section: Technical Solutionsmentioning
confidence: 99%
“…Two of them are from connections of group one and the two others are related to the connections of group two. Characteristics of the specimens are presented in Table 4 for every specimen [7,8].…”
Section: Connection Geometrymentioning
confidence: 99%